Microbial Disease Spectrum Linked to a Novel IL-12Rβ1 N-Terminal Signal Peptide Stop-Gain Homozygous Mutation with Paradoxical Receptor Cell-Surface Expression - Louvain de Souza, Thais; de Souza Campos Fernandes, Regina C.; Azevedo da Silva, Juliana; Gomes Alves Júnior, Vladimir; Gomes Coelho, Adelia; Souza Faria, Afonso C.; Moreira Salomão Simão, Nabia M.; Souto Filho, João T.; Deswarte, Caroline; Boisson-Dupuis, Stéphanie; Torgerson, Dara; Casanova, Jean-Laurent; et al. (Frontiers in Microbiology, 2017)
Patients with Mendelian Susceptibility to Mycobacterial Diseases (MSMD) exhibit variable vulnerability to infections by mycobacteria and other intramacrophagic bacteria (e.g., Salmonella and Klebsiella) and fungi (e.g., Histoplasma, Candida, Paracoccidioides, Coccidioides, and Cryptococcus). The hallmark of MSMD is the inherited impaired production of interferon gamma (IFN-γ) or the lack of response to it. Mutations in the interleukin (IL)-12 receptor subunit beta 1 (IL12RB1) gene accounts for 38% of cases of MSMD. Most IL12RB1 pathogenic allele mutations, including ten known stop-gain variants, cause IL-12Rβ1 complete deficiency (immunodeficiency-30, IMD30) by knocking out receptor cell-surface expression. IL12RB1 loss-of-function genotypes impair both IL-12 and IL-23 responses. Here, we assess the health effects of a rare, novel IL12RB1 stop-gain homozygous genotype with paradoxical IL-12Rβ1 cell-surface expression. We appraise four MSMD children from three unrelated Brazilian kindreds by clinical consultation, medical records, and genetic and immunologic studies. The clinical spectrum narrowed down to Bacillus Calmette-Guerin (BCG) vaccine-related suppurative adenitis in all patients with one death, and recrudescence in two, histoplasmosis, and recurrence in one patient, extraintestinal salmonellosis in one child, and cutaneous vasculitis in another. In three patients, we established the homozygous Trp7Ter predicted loss-of-function inherited genotype and inferred it from the heterozygote parents of the fourth case. The Trp7Ter mutation maps to the predicted IL-12Rβ1 N-terminal signal peptide sequence. BCG- or phytohemagglutinin-blasts from the three patients have reduced cell-surface expression of IL-12Rβ1 with impaired production of IFN-γ and IL-17A. Screening of 227 unrelated healthy subjects from the same geographic region revealed one heterozygous genotype (allele frequency 0.0022) versus one in over 670,000 public genome/exomes. We also show that the carriers bear European ancestry-informative alleles and share the extended CACCAGTCCGG IL12RB1 haplotype that occurs worldwide with a frequency of 8.4%. We conclude that the novel IL12RB1 N-terminal signal peptide stop-gain loss-of-function homozygous genotype confers IL-12Rβ1 deficiency with varying severity and early-onset age through diminished cell-surface expression of an impaired IL-12Rβ1 polypeptide. We firmly recommend attending to warning signs of IMD30 in children who are HIV-1 negative with a history of adverse effects to the BCG vaccine and presenting with recurrent Histoplasma spp. and extraintestinal Salmonella spp infections.